2013
DOI: 10.1016/j.mcn.2012.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Glial cell line-derived neurotrophic factor (GDNF) induces neuritogenesis in the cochlear spiral ganglion via neural cell adhesion molecule (NCAM)

Abstract: Glial cell line-derived neurotrophic factor (GDNF) increases survival and neurite extension of spiral ganglion neurons (SGNs), the primary neurons of the auditory system, via yet unknown signaling mechanisms. In other cell types, signaling is achieved by the GPI-linked GDNF family receptor α1 (GFRα1) via recruitment of transmembrane receptors: Ret (re-arranged during transformation) and/or NCAM (neural cell adhesion molecule). Here we show that GDNF enhances neuritogenesis in organotypic cultures of spiral gan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 51 publications
1
36
0
Order By: Relevance
“…RET activates the PI3K/AKT, MEK/ERK, and SRC pathways, and NCAM activates the FYN/FAK pathway. Through these downstream targets, GDNF prevents apoptosis and promotes proliferation and differentiation in neurons (33,34,(38)(39)(40), ureteric bud (35,36), and spermatogonial SCs (37). Our results show that GDNF and its receptor, GFRα1, are found primarily in SSCs, suggesting that GDNF mainly acts as an autocrine factor.…”
Section: Sca1mentioning
confidence: 59%
See 1 more Smart Citation
“…RET activates the PI3K/AKT, MEK/ERK, and SRC pathways, and NCAM activates the FYN/FAK pathway. Through these downstream targets, GDNF prevents apoptosis and promotes proliferation and differentiation in neurons (33,34,(38)(39)(40), ureteric bud (35,36), and spermatogonial SCs (37). Our results show that GDNF and its receptor, GFRα1, are found primarily in SSCs, suggesting that GDNF mainly acts as an autocrine factor.…”
Section: Sca1mentioning
confidence: 59%
“…GDNF preferentially binds to the GDNF family receptor α 1 (GFRα1), which mediates the activation of the RET receptor tyrosine kinase and functions through the PI3K/AKT, MEK/ERK and SRC pathways in neurons (33,34), ureteric buds (35,36), and spermatogonial SCs (37). Recent studies indicated that the neural cell adhesion molecule (NCAM) and the downstream targets FYN/FAK may function as alternative pathways for GDNF in regulating axonal guidance and corneal regeneration (38)(39)(40)(41).…”
Section: Gdnf Does Not Function As a Radio Protector In Smgmentioning
confidence: 99%
“…On the other hand, we found NCAM to be co-expressed with GFRα1 in embryonic PCs, and in situ PLA experiments indicated that they are associated in vivo. Earlier work has shown that the GFRα1/NCAM complex provides a high-affinity binding site for GDNF (Paratcha et al., 2003) and mediates effects of this ligand on cell migration, neurite outgrowth, and axon guidance (Charoy et al., 2012, Duveau and Fritschy, 2010, Euteneuer et al., 2013, Paratcha et al., 2006). Having ruled out an effect of GDNF on embryonic PC migration, we considered possible direct effects of GFRα1 on NCAM function independently of GDNF.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the cellular mechanism by which NrCAM influences type I SG neurite growth could be probed using cell signaling inhibitors, as we have used for other guidance factors (e.g., Aletsee et al 2001; Mullen et al 2012; Euteneuer et al 2013). …”
Section: Discussionmentioning
confidence: 99%